PHRASEOLOGY DISCOURSE IN AIR TRAFFIC CONTROLLER'S COMMUNICATION - Khairunnisa Batubara (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
ABSTRACT This writing deals with the types of phraseology in air traffic controller’s communication. The objective of this writing is to find out the types of phraseology used in communication between ATC of KNIA and pilot. The source of this writing is an air traffic controller of KNIA. The data of this writing are the communication between controller and pilot which spoken in statements or commands called phraseology (words and phrases). Descriptive qualitative method is applied as a qualitative design in conducting this research. The instrument of data collection is voice recorder to record the data. Keywords: phraseology, air traffic controller, communication